2021
DOI: 10.3390/ijerph18020411
|View full text |Cite
|
Sign up to set email alerts
|

Safety Program Elements in the Construction Industry: The Case of Iraq

Abstract: The construction industries’ unsafe conditions require increased efforts to improve safety performance to prevent and reduce accident rates. Safety performance in the Iraqi construction industry is notoriously poor. Despite this condition, safety research has so far been neglected. Implementing a safety program is a proven initial step to improve safety. Therefore, the aim of this study is to identify the key elements of a safety program in the Iraqi construction industry. To verify and validate a list of safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…shows whether the consultation and grievance mechanism influence the aspect of management and maintenance of construction welfare facilities, the results reveal that the impact is important with an average index of 3.14 and 3.03. From the results obtained a intial conccurens can be cocncluded with previous research concducted in scope of management and maintenece criteras, the results resamble some simliartes in the Gulf region countreis that share a typical view on management knowloodge and maintence installation at construction projects [7], [11], [15], [35], [36], [46]. Table 5 shows the safety and health consequences.…”
Section: Detailed Management Aspects and Maintenance Implementation On Construction Welfare Facilitiesmentioning
confidence: 53%
See 3 more Smart Citations
“…shows whether the consultation and grievance mechanism influence the aspect of management and maintenance of construction welfare facilities, the results reveal that the impact is important with an average index of 3.14 and 3.03. From the results obtained a intial conccurens can be cocncluded with previous research concducted in scope of management and maintenece criteras, the results resamble some simliartes in the Gulf region countreis that share a typical view on management knowloodge and maintence installation at construction projects [7], [11], [15], [35], [36], [46]. Table 5 shows the safety and health consequences.…”
Section: Detailed Management Aspects and Maintenance Implementation On Construction Welfare Facilitiesmentioning
confidence: 53%
“…The work in the construction sector is most hazardous and vulnerable because of poor employment conditions characterized by way of its informal nature, the brief relationship between company and employee, unsure working hours, lack of primary services, and inadequacy of welfare facilities [2], [11], [22], [23]. Contractors in Iraq regularly disregard the fundamental necessities for welfare services.…”
Section: Construction Safety Practice In Iraqmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers, in various studies, have shown that the fatality rate in the construction industry is high [10]. The negative impact of poor safety performance is represented by the affects on time, cost, and productivity [11]. Therefore, there is a need for the implementation of an effective safety program to improve safety performance.…”
Section: Introductionmentioning
confidence: 99%